ECOSOFIAS E PRÁTICAS DE SUSTENTABILIDADE EM ESCOLAS DA EDUCAÇÃO BÁSICA NO BRASIL E NA AUSTRÁLIA - Rezende, Fernanda Freitas (2020)
This research takes the concept of ecosophy coined by Felix Guattari (1989) and tries to focus on two different realities, Brazil and Australia, and does not refer to its object of research: how schools recorded or not with official programs proliferated